High-rate lithium-ion battery performance of a ternary sea urchin-shaped CoNiO2@NiP6Mo18/CNTs composites - Cui, Li-ping; Sun, Shuang; Yu, Kai; Zhang, Shu; Wang, Mei-lin; Chen, Jia-jia; Zhou, Bai-bin (Journal of energy chemistry, 2024)
Polyoxometalates (POMs) act as electron sponges, enhancing reversible electron transfer and ensuring structural protection of urchin-shaped CoNiO2 nanospheres via CNTs assistance. CoNiO2@NiP6Mo18/CNTs demonstrates superior energy storage properties as anodes for lithium-ion batteries (LIBs). [Display omitted] Bimetallic oxides are attractive anode materials for lithium-ion batteries (LIBs) due to their large theoretical capacity. However, the low conductivity, short cycle life, and poor rate capability are the bottlenecks for their further applications. To overcome above issues, the basket-like polymolybdate (NiP6Mo18) and carbon nanotubes (CNTs) were uniformly embedded on the urchin-shaped CoNiO2 nanospheres to yield a ternary composites CoNiO2@NiP6Mo18/CNTs via electrostatic adsorption. The multi-level morphology of urchin spinules accelerates the diffusion rate of Li+; CNT improves the conductivity and enhances cycle stability of the material; and heteropoly acid contributes more redox activity centres. Thus, CoNiO2@NiP6Mo18/CNTs as an anode of LIBs exhibits a high initial capacity (1396.7 mA h g−1 at 0.1 A g−1), long-term cycling stability (750.2 mA h g−1 after 300 cycles), and rate performance (450.3 mA h g−1 at 2 A g−1), which are superior to reported metallic oxides anode of LIBs. The density functional theory (DFT) and kinetic mechanism suggest that CoNiO2@NiP6Mo18/CNTs delivers an outstanding pseudocapacitance and rapid Li+ diffusion behaviors, which is due to the rich surface area of the urchin-like CoNiO2 with the uniform embeddedness of NiP6Mo18 and CNTs. This study provides a new idea for optimizing the performance of bimetallic oxides and developing high-rate lithium-ion battery composites.